Security and Performance Analysis of Caesar and Vigenère Ciphers - Yandi Anzari; Teuku Djauhari; Tomi kurniawan; Noni Rahmawati; Niko Akbar (Journal of Intelligent Systems and Information Technology, 2026)
While most cryptographic benchmarks prioritize modern algorithms, this study offers a distinct, controlled evaluation of classical monoalphabetic versus polyalphabetic substitution ciphers under systematically scaled data workloads up to 1,000 KB. The objective is to quantify the exact execution throughput and security thresholds of the Caesar and Vigenère ciphers against contemporary automated attacks. The methodology utilizes programmatically built Python modules tested across 100 continuous trials inside an isolated Linux environment, subjected to automated brute-force scripts and statistical Kasiski examinations. The empirical results reveal that both algorithms exhibit linear time complexity, though the Vigenère cipher suffers a 38% to 45% performance overhead due to index alignment. Crucially, while the Vigenère cipher successfully deters primitive brute-force attacks, its structural security collapses catastrophically with a 100% vulnerability rate under statistical cryptanalysis once the file size reaches 50 KB. The practical implication dictates that polyalphabetic substitution provides superficial protection against modern computing power, reinforcing institutional policy to restrict these foundational algorithms exclusively to pedagogical frameworks rather than active information systems.